5(y-2)=6(y-1)

Simple and best practice solution for 5(y-2)=6(y-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y-2)=6(y-1) equation:


Simplifying
5(y + -2) = 6(y + -1)

Reorder the terms:
5(-2 + y) = 6(y + -1)
(-2 * 5 + y * 5) = 6(y + -1)
(-10 + 5y) = 6(y + -1)

Reorder the terms:
-10 + 5y = 6(-1 + y)
-10 + 5y = (-1 * 6 + y * 6)
-10 + 5y = (-6 + 6y)

Solving
-10 + 5y = -6 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-10 + 5y + -6y = -6 + 6y + -6y

Combine like terms: 5y + -6y = -1y
-10 + -1y = -6 + 6y + -6y

Combine like terms: 6y + -6y = 0
-10 + -1y = -6 + 0
-10 + -1y = -6

Add '10' to each side of the equation.
-10 + 10 + -1y = -6 + 10

Combine like terms: -10 + 10 = 0
0 + -1y = -6 + 10
-1y = -6 + 10

Combine like terms: -6 + 10 = 4
-1y = 4

Divide each side by '-1'.
y = -4

Simplifying
y = -4

See similar equations:

| 3(2k+18)=6(9+k) | | 4x^2+56x+156=0 | | s=4s-60 | | 9x-20=7x+16 | | 140=(2x-2)(2x+2) | | 6(5-5y)= | | t^3+t=4930 | | 2z/2= | | 11+x+24=19+x+22 | | 0.75(4x+8)=-3 | | 5k-15+j=3j-5 | | 3(2g+7m)= | | (x+x)-20x+100=0 | | 0.2r=-8 | | v+53=3v+21 | | 9=5.4*x | | 5y^2+7y-4=0 | | 12-4p=-4(-5p-3) | | (5x-15)=what | | 5y-2=3x+2 | | 4(-2f-6g)= | | 3x=2.52 | | 140=4x^2-4+4-16 | | x^1000=0.9 | | 3y=-x+0 | | 13w+16w-7+5=-5w+5-7 | | 4x^2-156=0 | | 8(-4k-4)=-5k-32 | | 3(3+2j)= | | 3z-35=5z-87 | | 5m-13=n+5 | | u=2u-74 |

Equations solver categories